Gestión del capital de trabajo y el desempeño financiero en las cooperativas de transportes de la ciudad de Loja, estudio de caso: Cooperativa de Transportes Loja, período 2019-2020 - Pineda López, Paulina Cecilia (2022)
The objective of this research work was to analyze the management of working capital and financial performance in transport cooperatives in the city of Loja. The case study: Cooperativa de Transportes Loja, Period 2019-2020, for which we considered as a sample the entire population, which comprises managers of cooperatives that provide passenger and cargo transport services, interprovincial modality, which have obtained the operating permit in the city of Loja. After implementing structured interviews, we determined that most of these companies do not consider working capital nor use financial indexes to measure their performance. The type of design used in the research is non-experimental because the variables are not manipulated or controlled. With the financial statements provided by the company, we applied financial indicators for which we used the mathematical method, which allowed through formulas to measure the independent and dependent variables with the resulting data. We concluded that the cooperative maintained a cash conversion period of 127.69 days in 2020 and 67.76 days in 2019, demonstrating deficiencies in administering each of the items comprising part of the working capital. Regarding its financial situation, the return on assets (ROA) was -5.43% (2020) and -0.48% (2019), and the return on equity (ROE) was -14.74% (2020) and -1.22% (2019); these negative results indicate the company's inability to generate profits and returns to the partners from the assets it has. For the company to maintain adequate control of its working capital, we proposed strategies for managing short-term assets and liabilities